2021
DOI: 10.3390/healthcare9050613
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of General Practitioners’ Attitudes and Beliefs about Psychological Intervention and the Medicine-Psychology Relationship in Primary Care: Toward a New Comprehensive Approach to Primary Health Care

Abstract: The biopsychosocial paradigm is a model of care that has been proposed in order to improve the effectiveness of health care by promoting collaboration between different professions and disciplines. However, its application still faces several issues. A quantitative–qualitative survey was conducted on a sample of general practitioners (GPs) from Milan, Italy, to investigate their attitudes and beliefs regarding the role of the psychologist, the approach adopted to manage psychological diseases, and their experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
2
0
2
Order By: Relevance
“…Most GPs reported that a lack of technique in behavioural medicine and psychological intervention is their main obstacle in their practice. In the long term, comprehensive primary healthcare models focusing on the person and their relational networks, adopting a life-long, promoting, preventive and curative vision, and taking into account the biological dimensions of the disease together with the individual social aspects should be taken into consideration for improving continuity of services in China [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most GPs reported that a lack of technique in behavioural medicine and psychological intervention is their main obstacle in their practice. In the long term, comprehensive primary healthcare models focusing on the person and their relational networks, adopting a life-long, promoting, preventive and curative vision, and taking into account the biological dimensions of the disease together with the individual social aspects should be taken into consideration for improving continuity of services in China [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that this cooperation is feasible but requires a period of adaptation between the two professionals (Solano et al, 2009). Nonetheless, even in recent years, Italian physicians view referrals to psychologists as the only form of collaboration and rarely use the in-office consultation option (Negri et al, 2021).…”
Section: Collaboration Between Physicians and Mental Health Professio...mentioning
confidence: 99%
“…9 Perawat dan dokter sangat berkontribusi terhadap perawatan pasien, tetapi sering tidak menghargai peran satu sama lain. 10 Dalam penelitian sebelumnya, dokter dan perawat memandang kolaborasi secara berbeda, dokter melihat kolaborasi sebagai mengikuti instruksi dan perintah, sementara perawat melihatnya sebagai peran pelengkap lebih signifikan daripada dokter. 11 Sikap positif profesional kesehatan terhadap IPC merupakan dasar keberhasilan implementasi IPC.…”
Section: Pendahuluanunclassified